Etika Pelayanan Publik Untuk Mewujudkan Good Governance di Polres Pelabuhan Tanjung Perak Kota Surabaya: Etika Pelayanan Publik Untuk Mewujudkan Good Governance di Polres Pelabuhan Tanjung Perak Kota Surabaya - Yuniar, Ibra; Prasetijowati, Tri; Kurniawan, Bagus Ananda (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2025)
This study aims to analyze the implementation of public service ethics in realizing good governance at the Tanjung Perak Port Police Department, Surabaya. The research is motivated by the ongoing bureaucratic reform and the increasing public demand for transparent, accountable, and integrity-based public services. A qualitative descriptive method was employed, with data collected through in-depth interviews, field observations, and documentation of policies and public service procedures.The findings indicate that the implementation of public service ethics at the Tanjung Perak Port Police has been relatively effective. This is reflected in the application of key principles such as transparency, accountability, participation, equality, conditionality, and the balance of rights and obligations between officers and the public. The main factors supporting this implementation include personnel integrity and competence, leadership commitment, organizational culture, infrastructure, and consistent internal supervision.The study concludes that strengthening ethical awareness among officers and enhancing public participation are essential to building a clean, professional, and just governance system within the police institution. Therefore, public service ethics not only serve as a moral foundation for bureaucratic behavior but also as a strategic instrument to reinforce public trust and institutional legitimacy in the implementation of good governance.